Change Order No. 3 to Specification 76-PW-10, Schedule "B" for Construction of Hueneme Road Relief Sanitary Pipeline - R. Dennis Hogle:::::: (1977)
A memorandum discussing changes to a contract for the construction of a sanitary pipeline.